Performing heritage: rethinking authenticity in tourism - Zhu, Yujie (Annals of tourism research, 2012)
This paper explores how the dongba as the ritual practitioner perceives his authenticity during the marriage ceremony in the Naxi Wedding Courtyard in Lijiang, China. Through the dongba’s life story, the paper indicates that, the power of his making judgment is not entirely related to the toured objects, socially constructed reality or the existential feeling, but also has to do with what happens in between. The ritual performance, integrated with the external world, gives rise to the performative experience of the authenticity and offers a deep understanding of the link between memory, habitus and embodied practice. The dynamic process of “becoming” authentic weaves the interaction between the individual agency and the reality.